Exploring why and how encounters with the Norwegian health-care system can be considered culturally unsafe by North Sami-speaking patients and relatives: A qualitative study based on 11 interviews - Mehus, Grete; Bongo, Berit Andersdatter; Engnes, Janne Isaksen; Moffitt, Pertice (International Journal of Circumpolar Health, 2019)
Source at https://doi.org/10.1080/22423982.2019.1612703 . Background - Citizens of Norway have free and equal access to healthcare. Nurses are expected to be culturally sensitive and have cultural knowledge in encounters with patients. Culturally safe care is considered both a process and an outcome, evaluated by whether the patients feel safe, empowered and cared for, or not. All patients request equal access to quality care in Norway, also Sami patients. Objectives - The aim of the study is to identify whether Sami patients and relatives feel culturally safe in encounters with healthcare, and if not, what are the main concerns. Methods - This qualitative study used semi-structured interviews in the North Sami language, with 11 North Sami participants.The transcribed data were analysed through a lens of cultural safety by content analysis. Findings - Data analysis explicated themes including: use of Sami language, Sami identity and cultural practices, connections to positive health outcomes to enhance cultural safe care and well-being for North-Sami people encountering the Norwegian health-care system. Conclusion - Culturally safe practices at the institutional, group and individual levels are essential to the well-being of Sami people. An engagement in culturally safe practices will facilitate (or) fulfil political and jurisdictional promises made to the Sami people, consequently improving positive impact of healthcare.